Age-associated augmented renal clearance and low BMI trigger suboptimal vancomycin trough concentrations in children with haematologic diseases: data of 1453 paediatric patients from 2017 to 2022 - Fengjiao Wang; Mi Zhou; Wenjuan Wang; Zengyan Zhu; Yinghui Yan (BMC Pediatrics, 2023)
Abstract Background It is usually difficult for the trough concentration of vancomycin to reach the recommended lower limit of 10 mg/L per the label dose in the paediatric population. Moreover, children with haematologic diseases who suffer from neutropenia are more likely to have lower exposure of vancomycin, and the risk factors have been poorly explored. Method We reviewed and analysed the initial trough concentration of vancomycin and synchronous cytometry and biochemical parameters in the blood of 1453 paediatric patients with haematologic diseases over a 6 year period, from 2017 to 2022. Results Forty-five percent of the enrolled children had vancomycin trough concentrations below 5 mg/L after receiving a dose of 40 mg/kg/day, and the multiple regression showed that age (OR = 0.881, 95% CI 0.855 to 0.909, P < 0.001), BMI (OR = 0.941, 95% CI 0.904 to 0.980, P = 0.003) and the glomerular filtration rate (OR = 1.006, 95% CI 1.004 to 1.008, P < 0.001) were independent risk factors. A total of 79.7% of the children experienced augmented renal clearance, which was closely correlated to age-associated levels of serum creatinine. The vancomycin trough concentration was higher in children with aplastic anaemia than in those with other haematologic diseases due to a higher BMI and a lower glomerular filtration rate. Conclusion Age-associated augmented renal clearance and low BMI values contributed to suboptimal trough concentrations of vancomycin in children with haematologic diseases, and the effects of long-term use of cyclosporine and glucocorticoids need to be taken into account.